# Factor -8x^{3} - 2x^{2} - 12x - 3 by grouping. What is the resulting expression?

**Solution:**

The given polynomial is -8x^{3} - 2x^{2} - 12x - 3

Now let us group the first two and last two terms

= (-8x^{3} - 2x^{2}) - (12x - 3)

From each binomial, let us take out the GCF

= -2x^{2}(4x + 1) - 3(4x + 1)

Now the resulting expression is

= (4x + 1)(-2x^{2} - 3)

= -(4x + 1)(2x^{2} + 3)

Therefore, the resulting expression = -(4x + 1)(2x^{2} + 3).

## Factor -8x^{3} - 2x^{2} - 12x - 3 by grouping. What is the resulting expression?

**Summary:**

Factor -8x^{3} - 2x^{2} - 12x - 3 by grouping. The resulting expression is -(4x + 1)(2x^{2} + 3)

Math worksheets and

visual curriculum

visual curriculum